Electrode-tool for Making Holes on Helical Trajectories by EDM. (2016) - Soaita, Dumitru
Abstract: The technical problem which this paper proposes to solve is the design and manufacturing of tooling for machining electrodes for long helical trajectories holes by electric discharge machining (EDM). The shape of the electrode proposed contains several demands like: constant pitch helical type; tubular section as well as concentric and coaxial relationship between the component part, the active electrode and its tail and to be able to accurately produce helical trajectories holes with great length. The geometric parameters of the tool-electrode proposed have high versatility; the electrode can be used on any universal CNC EDM machine that is capable to achieve inner helical interpolation.